Effects of Omalizumab on FcεRI and IgE Expression in Lesional Skin of Bullous Pemphigoid - Seyed Jafari, S. Morteza (Front Immunol, 2019)
Recent studies suggest an important role of immunoglobulin E (IgE) as an alternative pathogenic pathway in the development of bullous pemphigoid (BP), as the most frequent subepidermal blistering disease of the skin Use of IgE targeted therapies, such as omalizumab, has been shown promising in recent studies. The aim of this study was to assess the effect of omalizumab on FcεRI and IgE expression on circulating basophils and on lesional intradermal cells in BP to generate insight into the immunological effects of omalizumab in BP. We report two cases of BP patients treated with omalizumab. Efficacy of treatment was assessed clinically 4 months after initiation of the therapy. Lesional and non-lesional skin biopsies where taken before and 4 weeks after initiation of omalizumab therapy. In addition, FcεRI expression on circulating cells and IgE levels in serum and in the skin samples, as well as anti-BP180 and anti-BP230 in serum and eosinophils and basophils counts in blood were assessed before and during treatment. Both patients showed a marked improvement after 4 months, with no adverse effects. Down-regulation of FcεRI, IgE in lesional skin and on circulating basophils were observed in parallel with clinical improvement. The current case study supports the role of omalizumab in the treatment of a subset of BP patients. Our observations suggest that omalizumab represents a valuable therapeutic option in the management of BP patients. Its efficacy might be related to reduction in FcεRI+ and IgE+ basophils and intradermal cells.